Aspectos ecológicos del cáncer gástrico en Costa Rica - Sierra Ramos, Rafaela (1983)
An analysis of 1315 cases of gastric cancer from the records of the Ministry of Public Health, San Jose, Costa Rica between 1977 and 1980 showed important geographical differences in the incidence, and especially in relation to the sex ratio, age structure and migratory patterns. Rates of incidence ranged between 12.6 and 153.2 per 100,000 inhabitants in men and 10.6 and 56.6 in women. Variations in the incidence of gastric cancer rates were studied in relation to ecological parameters, including certain soil and drinking water characteristics as well as the presence of vitamins A and C in serum. No significant relation was found between gastric cancer rates and the presence of vitamins and of several components in drinking water. However, a multivariate analysis considering nine soil components and pH showed a statistically significant (P< 0.01) association with pH, K, Zn and Fe, which account for 22% of the variation in the incidence rates. A dynamic and multifactorial model is proposed to explain regional variations in cancer rates, with a tentative application of this model to the results obtained